Rural Tourism: A Grounded Theory on Limited Stakeholder Advocacy - Sebby, Angela; Jordan, Kenneth (Archives of Business Research, 2018)
While many rural areas in the southeast look to tourism to help supplement diminishing financial opportunities due to the decline in manufacturing and farming, many communities still incur obstacles and are unable to sustain a viable tourist destination area. Without entrusting the Destination Marketing Organization (DMO) to identify stakeholders’ contributions for the betterment of the community as a destination brand and visitor demands, expectations cannot be met. Working within small-town politics, nativity of the benefits of tourism, and misaligned brand images, the DMOs and stakeholders appear ineffective in marketing the rural area as a destination that fully embodies the culture, history, and natural resources contained within their respective geographic boundaries. Understanding how to build and obtain stakeholders’ confidence, a DMO can cultivate strategic relationships through social exchanges and strengthen trust within stakeholder groups. These relationships sustain an all-inclusive brand image for the rural destination area, increasing visitor satisfaction, and stakeholder investment.